Pastoral Accompaniment for Congregants Experiencing Relational Crisis Due to Digital Communication - Apin Militia Christi; Yosua Imanuel; Yustina Marampa (International Perspectives in Christian Education and Philosophy, 2024)
Digital communication has become part of the everyday fabric of congregational life. While it enables connection and pastoral accessibility, it also introduces relational tensions through divided attention, interpretive ambiguity, social comparison, online jealousy, concealed messaging, and the weakening of face-to-face reconciliation. This conceptual research article examines pastoral accompaniment for Christian congregants who experience relational crises caused or intensified by digital communication. The study aims to construct a pastoral framework that is theologically grounded, psychologically informed, ethically responsible, and usable in church ministry. Using an integrative literature review, the article synthesizes scholarship on digital religion, computer-mediated communication, relational conflict, phubbing, technoference, online counseling ethics, and practical theology. The synthesis indicates that digital relational crisis should not be reduced to excessive screen use. It is more accurately understood as a crisis of presence, attention, trust, boundaries, and interpretive charity. The article proposes pastoral accompaniment as a hybrid care that combines attentive presence, relational discernment, digital boundary formation, covenantal communication practices, and ethically bounded use of online media. It concludes that churches need to move beyond reactive counseling toward preventive digital discipleship that forms congregants in truthful speech, faithful presence, confidentiality, and relational accountability.